Antibiogram and Genes Contributing to Virulence in E. coli Isolated From Clinical Cases of Colibacillosis in Broilers - Paudyal, Narayan; Basyal, Sanjog; Pun, Laxmi; Thapa, Nita; Munakarmi, Reshmi; Pokhrel, Rabin (Journal of Agriculture and Forestry University, 2026)
Escherichia coli causes colibacillosis in poultry, leading to significant economic losses through reduced productivity, high mortality, and carcass condemnation. The frequent and often indiscriminate use of antibiotics in poultry production has promoted the emergence of multi-drug resistant (MDR) bacterial strains, complicating their treatment. This study aimed to determine the antibiogram and virulence genes of E. coli isolated from clinical cases of colibacillosis. A total of 102 E. coli isolates were cultured on Eosin Methylene Blue (EMB) agar and subjected to antibiotic susceptibility testing using the Kirby–Bauer disc diffusion method with 16 antibiotics from 8 different classes. Isolates resistant to three or more antibiotic classes were classified as MDR. Polymerase chain reaction (PCR) was employed to detect six virulence-associated genes, namely iss, iroN, iucC, cvaC, tsh and yjj. High resistance was observed against enrofloxacin (99%) followed by cefoxitin (90.2%), tetracycline (86.3%), erythromycin (79.4%), amoxycillin (77.5%), doxycycline (76.5%) and ciprofloxacin (75.5%) while greater susceptibility was noted to azithromycin (67.6%), followed by ceftriaxone (65.7%), norfloxacin (53.9%) and amikacin (51%). Overall, 82.3% of isolates were detected to be MDR. Among virulence genes, yjj (58.82%) was the most prevalent. Besides, iss, iroN, iucC, tsh and cvaC were PCR positive in 48.04%, 45.10%, 31.37%, 19.61% and 10.78%, respectively. The coexistence of multiple virulence-associated genes in Avian Pathogenic Escherichia coli (APEC) isolates with a high multiple antibiotic resistance (MAR) index indicates high selection pressure on broiler farms. This could be a cause for the antibiotic therapy failure, commonly encountered in the broiler farms of the sampling areas.